A, a^3=27=>x=3
B, (2x-1)^3=-8=>x=-0,5
C,(x+3)^2=49=>x=4
D,(x-2)^2=36=>x=4
x^3=27=>x=3
b,(2x-1)^3=-8
=>2x-1=-2
=>2x=-1
x=-3/2
C(x+3)^2=49=>x+3=7
=>x+3=7=>x=4
D(x-2)^2=36=>x=6
x-2=6=>x=8
a) \(x^3=27\)
\(\Rightarrow3^3=27\)
\(\Rightarrow x=3\)
b)\(\left(2x-1\right)^3=-8\)
\(\left(2x-1\right)^3=\left(-2\right)^3\)
\(\Rightarrow2x-1=-2\)
\(\Rightarrow x=-\frac{1}{2}\)
c)\(\left(x+3\right)^2=49\)
\(\left(x+3\right)^2=7^2\)
\(\Rightarrow x+3=7\)
\(\Rightarrow x=4\)
d) \(\left(x-2\right)^2=36\)
\(\left(x-2\right)^2=6^2\)
\(\Rightarrow x-2=6\)
\(\Rightarrow x=4\)
nha^_^
tks!!
@@@@